2014
DOI: 10.3892/etm.2014.1972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ECRG2 in combination with cisplatin on the proliferation and apoptosis of EC9706 cells

Abstract: The aim of the present study was to explore the effect of esophageal cancer-related gene 2 (ECRG2) protein in combination with cisplatin (DDP) on the proliferation and apoptosis of esophageal cancer cells. A 3-(4, 5-dimethylthiazol-2-yl) 2,5-diphenyltetrazolium bromide (MTT) assay was used to examine the effects of ECRG2 alone and ECRG2 in combination with DDP on the proliferation of EC9706 esophageal cancer cells. Hoechst 33258 staining was performed to analyze the effects of ECRG2 alone and ECRG2 in combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…This study was approved and monitored by the Ethics Committees of the First Affiliated Hospital of Shantou Medical University. Human esophageal squamous cell carcinoma cell lines, EC109 [ 18 , 19 ] and EC9706 [ 20 , 21 ], were obtained from the Chinese Academy of Sciences and from The Cell Bank of Type Culture Collection of Chinese Academy of Sciences (CAS, Shanghai). Cells (1 × 10 5 ) were grown in RPMI1640 medium (ICN; Biomedicals Inc.) supplemented with 10% fetal calf serum, 100 units/ml penicillin and 100 units/ml streptomycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved and monitored by the Ethics Committees of the First Affiliated Hospital of Shantou Medical University. Human esophageal squamous cell carcinoma cell lines, EC109 [ 18 , 19 ] and EC9706 [ 20 , 21 ], were obtained from the Chinese Academy of Sciences and from The Cell Bank of Type Culture Collection of Chinese Academy of Sciences (CAS, Shanghai). Cells (1 × 10 5 ) were grown in RPMI1640 medium (ICN; Biomedicals Inc.) supplemented with 10% fetal calf serum, 100 units/ml penicillin and 100 units/ml streptomycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Cell morphology was observed under 340 nm excitation light using an inverted microscope (Olympus Company, Japan) (Song et al. 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, restoring ECRG2 expression and function in cancer cells is of great interest and an attractive therapeutic strategy. Several recent studies have investigated the effect of synthetic ECRG2 polypeptides on cultured cancer cells [ 66 , 67 ]. ECRG2 is a small protein of 85 amino acids; thus, its production is amenable to chemical synthesis.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…ECRG2 is a small protein of 85 amino acids; thus, its production is amenable to chemical synthesis. Studies by Song et al [ 66 , 68 ] showed that synthetic ECRG2 alone (8.5 µg/L) killed esophageal cancer cells (EC9706) in cell cultures by ~18–25% at 24 and 72 h time intervals. The synthetic ECRG2 was also able to enhance cisplatin-induced cell death in cisplatin-resistant esophageal cancer cells [ 67 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%